The Influence of Parenting, Financial Inclusion, and Financial Literacy on Financial Management of Gen-Z - Aisyah Nur aisyah; J. Junaidi; G. Goso (Golden Ratio of Finance Management, 2026)
This study aims to analyze the influence of parenting, financial inclusion, and financial literacy on the financial management of Generation Z students. Specifically, this study tests the hypothesis that parenting, financial inclusion, and financial literacy have a positive effect on financial management, and that financial literacy acts as a mediator. This study used a quantitative approach, involving 123 university students as respondents selected using a stratified random sampling technique. Data analysis was conducted using the covariance-based Structural Equation Modeling (SEM) method using AMOS 22 with SPSS 22. The results show that parenting and financial inclusion have a positive and significant effect on financial literacy. However, parenting and financial inclusion do not have a significant effect on financial management. Conversely, financial literacy has been shown to have a positive and significant effect on financial management and significantly mediates the effect of parenting and financial inclusion on financial management. These findings emphasize the central role of financial literacy in improving students' financial management skills. Therefore, strengthening financial literacy through synergy between families and educational institutions is an important strategy in shaping more adaptive financial behaviors in Generation Z.